2017
DOI: 10.1248/bpb.b16-00971
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative Activity of Hydrolysate from Rice Bran Protein in HepG2 Cells

Abstract: Glutathione (GSH) is an ubiquitous thiol-containing tripeptide, which plays important roles in cellular protection from oxidative stress. In our search for a dietary source that can increase GSH levels, we discovered that a 24 h treatment of HepG2 cells with rice bran protein hydrolysate (RBPH), prepared by Umamizyme G-catalyzed hydrolysis, increased the GSH content in a dose-dependent manner. RBPH elevated the expression levels of γ-glutamylcysteine synthetase (γ-GCS), which constitutes the rate-limiting enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Protein hydrolysates from rice, rice bran, eggshell membrane and chickpea have been reported to increase the intracellular glutathione levels and upregulate anti-oxidative enzymes in cells. ( 4 , 34 36 ) Since the active concentration ranged from 0.1 to 10 mg/ml, SLH showed similar bioactivity to the aforementioned hydrolysates (Fig. 4 A).…”
Section: Discussionmentioning
confidence: 74%
“…Protein hydrolysates from rice, rice bran, eggshell membrane and chickpea have been reported to increase the intracellular glutathione levels and upregulate anti-oxidative enzymes in cells. ( 4 , 34 36 ) Since the active concentration ranged from 0.1 to 10 mg/ml, SLH showed similar bioactivity to the aforementioned hydrolysates (Fig. 4 A).…”
Section: Discussionmentioning
confidence: 74%
“…For example, treatment with 5 mg/mL rice bran-hydrolysate for 24 h increased intracellular GSH levels in HepG2 cells by ca. 2-fold . A 12 h treatment with 2.5 or 5 mg/mL FSGHF3 increased mRNA levels of γ-GCSh by ca.…”
Section: Discussionmentioning
confidence: 92%
“…We reported that rice bran protein hydrolysate increases intracellular GSH levels in the HepG2 human hepatoblastoma cells. 17 Additionally, rice-derived peptides and sake lees hydrolysate are hepatoprotective in the case of acetaminophen (APAP)-induced liver injury. 18,19 These antioxidative effects were suggested to be mediated through the Nrf2 antioxidant pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies have demonstrated the extensive involvement of oxidative stress in ageing itself [4]. Oxidative stress represents an imbalance between toxic reactive oxygen species (ROS) and antioxidant systems, and high levels of ROS induce inflammation and cytotoxicity, which damages proteins, lipids, and DNA and subsequently disrupts mitochondrial structure and functions, ultimately resulting in cell death [5][6][7]. At present, most experts think it is related to the sudden onset of systemic inflammatory response syndrome in COVID-19 severe patients [8].…”
Section: Introductionmentioning
confidence: 99%